『醫方集解』처방 분류에 대한 고찰 - 송지청(Ji Chung Song); 정헌영(Heon Young Jeong); 금경수(Kyung Soo Keum) (동의생리병리학회지, 2010)
『Yifangjijie』 is a collection of prescription in Traditional Medicine, which was published in Qing dynasty. In this book, effectiveness of prescriptions 1s described by means of Meridians uniquely compared with any others. Therefore, I tried to pay attention to those explanations and arrange by Meridians and effectiveness of prescriptions. Classification by effectiveness of prescriptions has a few points of emphasis in Meridians and Classification of Meridians by effectiveness of prescriptions has intent in somehow. In this paper, authors will explain those classification KCI Citation Count: 1